Dermatan sulfate: new functions from an old glycosaminoglycan - Trowbridge, Janet M.; Gallo, Richard L. (Glycobiology (Oxford), 2002)
Glycosaminoglycans constitute a considerable fraction of the glycoconjugates found on cellular membranes and in the extracellular matrix of virtually all mammalian tissues. Their ability to bind and alter protein–protein interactions or enzymatic activity has identified them as important determinants of cellular responsiveness in development, homeostasis, and disease. Although heparan sulfate tends to be emphasized as the most biologically active glycosaminoglycan, dermatan sulfate is a particularly attractive subject for further study because it is expressed in many mammalian tissues and it is the predominant glycan present in skin. Dermatan and dermatan sulfate proteoglycans have also been implicated in cardiovascular disease, tumorigenesis, infection, wound repair, and fibrosis. Growing evidence suggests that this glycosaminoglycan, like the better studied heparin and heparan sulfate, is an important cofactor in a variety of cell behaviors.